The Synaptic Targeting of mGluR1 by Its Carboxyl-Terminal Domain Is Crucial for Cerebellar Function - Ohtani, Yoshiaki (J Neurosci, 2014)
The metabotropic glutamate receptor subtype 1 (mGluR1, Grm1) in cerebellar Purkinje cells (PCs) is essential for motor coordination and motor learning. At the synaptic level, mGluR1 has a critical role in long-term synaptic depression (LTD) at parallel fiber (PF)-PC synapses, and in developmental elimination of climbing fiber (CF)-PC synapses. mGluR1a, a predominant splice variant in PCs, has a long carboxyl (C)-terminal domain that interacts with Homer scaffolding proteins. Cerebellar roles of the C-terminal domain at both synaptic and behavior levels remain poorly understood. To address this question, we introduced a short variant, mGluR1b, which lacks this domain into PCs of mGluR1-knock-out (KO) mice (mGluR1b-rescue mice). In mGluR1b-rescue mice, mGluR1b showed dispersed perisynaptic distribution in PC spines. Importantly, mGluR1b-rescue mice exhibited impairments in inositol 1,4,5-trisphosphate receptor (IP(3)R)-mediated Ca(2+) release, CF synapse elimination, LTD induction, and delay eyeblink conditioning: they showed normal transient receptor potential canonical (TRPC) currents and normal motor coordination. In contrast, PC-specific rescue of mGluR1a restored all cerebellar defects of mGluR1-KO mice. We conclude that the long C-terminal domain of mGluR1a is required for the proper perisynaptic targeting of mGluR1, IP(3)R-mediated Ca(2+) release, CF synapse elimination, LTD, and motor learning, but not for TRPC currents and motor coordination.